Advanced seat suspension control system design for heavy duty vehicles - Du, Haiping, 1968- (Emerging Methodologies and Applications in Modelling, Identification and Control Ser., 2020)
This book provides systematic knowledge of the advanced seat suspension design and control for heavy duty vehicles. --